TEKUN Nasional HQ / Zairul Azri Zuhairi ... [et al.] - Zairul Azri, Zuhairi; Che Mohd Shafiq Aiman, Che Othman; Siti Nur Aqilah, Che Diharis; Alia Shaheera Ain, Kamaruddin; Rabitah, Khairul Aziz (2019)
This project examines the case study which is a medium rise mix development building which is Tekun Nasional Headquarter at Bandar Tasek Selatan. The aspects that will be covered in this project are the whole maintenance system which includes the maintenance organization, maintenance policy, the building design and concept, condition along with maintenance planning and programme and also the legal aspects and maintenance financial. The study is to determine the effectiveness of applied method towards the building in various aspects including law, management and finance. Through the study, few elements could be identified to play a huge role and give huge impact toward the maintenance of the building. Started with a well-organized maintenance organization to be responsible in managing the whole maintenance works to provide comfort to the occupants and sustainability to the building. The importance of maintenance policy and quality standard also considered to be one of the most important element in maintaining a building and the importance of maintenance planning and programme towards Tekun Nasional headquarter. As for maintenance financial management, the need of controlling income and expenditure in order to balance the need and to conserve and obtain optimum net profit. The most importantly to provide a better maintenance for the building Tekun Nasional Headquarter.